NLRP1 and NLRP3 polymorphisms in mesothelioma patients and asbestos exposed individuals a population-based autopsy study from North East Italy. - Borelli, Violetta; Moura, Ronal R; Trevisan, Elisa; Crovella, Sergio (Infect Agent Cancer, 2015)
NRLP1 (rs12150220, rs9889625, rs9900356, rs6502867, rs2670660) and NLRP3 (rs35829419, rs10754558) polymorphisms have been analyzed in 69 subjects with documented asbestos exposure and death for malignant pleural mesothelioma and 59 patients with documented asbestos exposure but death for other causes, all from a North East Italy. No association was found between NLRP1 and NLRP3 polymorphisms and susceptibility to develop mesothelioma using the general, dominant or recessive models. Also haplotype analysis did not reveal any significant association with mesothelioma. Our findings, being controversial with respect to another study on Italian patients, do suggest the need of further studies to unravel the contribution of NLRP1 and NLRP3 in susceptibility to mesothelioma.